Pushing Heterojunction Technology Further: Novel Metallization Processes and Architectures - Nicola Frasson; Marco Galiazzo (SiliconPV Conference Proceedings)
This work provides an overview on the different approaches to make Silicon Hetero-Junction cell (SHJ) production more scalable by investigating alternative metallization processes which can potentially be competitive with the standard Ag-based processes (Ag micro-size). With this purpose, this research aims at introducing the idea of widely using Ag-coated Cu formulations and/or low-Ag deposit solutions involving Ag nanoparticles-based formulations and reactive Ag (also referred as particle free) inks for both rear and front cell depositions on a single (finger and busbars) screen-printing process.